Early Diagnosis of Hearing Loss in Patients Under Methadone Maintenance Treatment - Bayat, Arash; Saki, Nader; Mirmomeni, Golshan; Yadollahpour, Ali (Frontiers in Neurology, 2019)
Background and Objective: Methadone maintenance treatment (MMT) as the most effective treatment for opioid addictions could induce both reversible and permanent hearing loss. Therefore, early detection of methadone-induced hearing loss is necessary to prevent irreversible cochlear damage. The present study aims to identify the early onset of hearing loss in patients who underwent MMT and to compare them with the age and gender matched normal hearing peers. Methods: This was an analytic cross-sectional study conducted on patients (n=27 males; age range: 18-53 years old) who received three-month MMT course (MMT group) and a control group consisting of age and gender matched healthy individuals (n= 27 males). Before MMT, all patients underwent conventional audiometry (250-8000 Hz) and those with normal hearing threshold participated into the study. One month after MMT termination, the patients were assessed for possible hearing loss using conventional pure tone audiometry (PTA), extended high frequency (EHF) audiometry, and distortion product otoacoustic emissions (DPOAEs). Results: Our results demonstrated that the mean EHF thresholds in the MMT patients were significantly greater than the age- and gender-matched heathy controls across all frequencies (p<0.001). However, there was no statistically significant difference in conventional PTA thresholds between both groups (p>0.05). DPOAE amplitudes significantly reduced at higher frequencies (3,000 Hz - 8,000 Hz) in the MMT group, compared to the healthy control group. In contrast to the conventional PTA audiometry, the EHF and DPOAE assessments identified hearing impairments in 11 (40.74%), and 14 (51.85%) of the MMT patients, respectively. The main mechanisms proposed for methadone induced hearing loss are cochlear ischemia following vasospasm or vasculitis, direct effect of opioids on opioid receptors present in cochlear stria vascularis of inner ear, blood-labyrinth selective transport of opioidproteins and receptors, and genetic polymorphism and mutations. Conclusion: The EHF and DPOAE tests have the potential to detect earlier changes in auditory function than conventional frequency audiometry in the MMT patients.